EFEKTIVITAS EDUKASI GIZI BERBASIS VIDEO TIKTOK TERHADAP PENGETAHUAN DAN SIKAP KONSUMSI GULA PADA REMAJA - Nur Fadilla; Nikmah Utami Dewi (Jurnal Genta Mulia, 2026)
Diabetes mellitus (DM) is a non-communicable disease characterized by chronic blood sugarelevation. Excessive consumption of foods and beverages high in added sugar is a major risk factor fortype 2 DM, especially in adolescents. Nutrition education through innovative media such as TikTokcan be an effective alternative to increase knowledge and change adolescent attitudes. To analyze theeffectiveness of nutrition education using TikTok videos on knowledge and attitudes toward sugarconsumption based on the Transtheoretical Model (TTM) theory in students. Quasi-experimentalresearch with pre-test post-test control group design. A sample of 40 students from MAN 1 Palu Citywas selected by purposive sampling, consisting of 20 students in the experimental group (TikTokeducation) and 20 students in the control group (instructional video). Data were analyzed usingPaired sample t-test and Independent sample t-test. There was a significant difference in knowledgescores in both groups (p-value = 0.000). Knowledge scores in the experimental group increased from52.80 to 73.60, while the control group increased from 50.80 to 74.60. Attitude scores showed nosignificant difference (p-value > 0.05), but there was a change in stages from contemplation topreparation based on TTM. Gain Score showed moderate effectiveness in both media (TikTok = 0.44;instructional video = 0.48). TikTok-based nutrition education and instructional videos are effective inincreasing knowledge and changing adolescent attitudes toward sugar consumption fromcontemplation to preparation stages.